Jaborá orthohantavirus in rodents of Alto Paraná Atlantic Forest: first description in Argentina - Bellomo, Carla María (2024)
The genus Orthohantavirusgroups rodent-borne hantaviruses, including non-pathogenic and pathogenic viruses. The latter include agents that cause hantavirus pulmonary syndrome (HPS), a severe disease endemic to the Americas. In northeastern Argentina, the first HPS cases were reported in Misiones province in 2003. The viruses Lechiguanas and Juquitiba were characterized from blood samples of HPS cases, but only the latter was found in rodents in the area. In neighboring areas of the Atlantic Forest in Brazil and Paraguay, Juquitiba and Jaborá viruses (JABV) were found associated with Oligoryzomys nigripesand Akodon montensis,respectively. We collected rodent samples from 2017 to 2020 and analyzed for IgG antibodies against hantavirus by ELISA. For the positive rodents, we extracted total RNA and performed reverse transcription-polymerase chain reaction (RT‐PCR) followed by a nested PCR. The phylogenetic analysis included 35 nucleotide sequences from the GenBank public repository. Of 746 captured rodents, IgG was detected in 14 A. montensis (28%, n=50). The viral genome amplification revealed a new orthohantavirus to Argentina. The genotype in consistent with the JABV found in neighboring countries.This paper reports JABV as a new orthohantavirus variant for Argentina, expanding the known range of this variant. This finding has public health relevance, because prevention is the main tool to avoid infection of humans.